0

8x - 8y equals 1 the solution for y is equals to?

Updated: 12/12/2022

Wiki User

13y ago

8x - 8y = 1

Add 8y to each side:

8x = 8y + 1

Subtract 1 from each side:

8x - 1 = 8y

Divide each side by 8:

y = x - (1/8)

Wiki User

13y ago

Earn +20 pts
Q: 8x - 8y equals 1 the solution for y is equals to?
Submit
Still have questions?
Related questions

No.

Is x equals 1 a solution of the equation 2 - 8x?

No. That is because 2 - 8x is an algebraic expression, not an equation. And since it is not an equation, it does not have a solution.

What is the solution to 8x-19 equals 3x plus 1?

8x - 19 = 3x + 1 5x -19 = 1 5x = 20 x = 4

What is -8y - 7 equals -8 plus 8y?

If: -8y-7 = -8+8y Then: -7+8 = 8y+8y And: 16y = 1 So: y = 1/16

What is the solution of -8x equals 32?

-8x = 32Divide each side by 8:-x = 4Multiply each side by -1:x = -4

What is the gradient in the equasion 4x-8y equals 12?

Rewrite the equation in the slope intercept form: y = mx + c Thus: 4x - 8y = 12 8y = 4x - 12 y = 4/8x - 12/8 = 1/2x - 3/2 and then, the gradient is the coefficient of x viz 1/2 or 0.5

What is the answer to 10x - 8y equals -2?

The answer to that is a graph, which I cannot show you (it's not possible on this text box). I will tell you the function form of the problem: y= -10/8x + 1/4

(1, 1)

What is the solution to x-8x equals 1?

x - 8x = 1 Perform the indicated subtraction on the left side: -7x = 1 Divide each side of the equation by -7 : x = - 1/7

What is the inverse function of y equals 8x plus 5?

The inverse function is obtained by interchanging corresponding values of x and y and then transposing the resulting equation to make y the subject. f(x) = y = 8x + 5 therefore f-1(x) = x = 8y + 5 : 8y = x - 5 : y = (x - 5)/8 The inverse function of y = 8x + 5 is y = (x - 5)/8

What are the values of x y and k when the line y equals kx plus 1 is a tangent to the curve y squared equals 8x?

I guess you mean the coordinates of the point of contact for x and y. The line is a tangent when the solution to where they meet has a repeated root, ie: y = kx + 1 &rarr; x = (y - 1)/k y&sup2; = 8x &rarr; y&sup2; = 8(y - 1)/k &rarr; ky&sup2; = 8y - 8 &rarr; ky&sup2; - 8y + 8 = 0 has repeated roots when the discriminant is zero, ie: 8&sup2; - 4 &times; k &times; 8 = 0 &rarr; 8 - 4k = 0 &rarr; k = 2 &rarr; point of contact is: 2y&sup2; - 8y + 8 = 0 &rarr; y&sup2; - 4y - 4 = 0 &rarr; (y - 2)&sup2; = 0 &rarr; y = 2 &rarr; 2 = 2x + 1 &rarr; 2x = 1 &larr; x = &frac12; &rarr; point of contact is (0.5, 2) and k = 2.

-1